Evaluation of symptoms and risks in stable chronic obstructive pulmonary disease patients with radiographic bronchiectasis - Rong-Bao Zhang (KeAi Communications Co., Ltd., 2017)
Objective: To investigate the presence of previously undiagnosed radiographic bronchiectasis in stable chronic obstructive pulmonary disease (COPD) patients using high resolution computed tomography (HRCT) and to evaluate the effect of radiographic bronchiectasis on the symptoms and risks in stable COPD patients. Methods: From May 2012 to April 2014, there were 347 patients enrolled in COPD database. Data describing the general conditions, the frequency of acute exacerbations the year before, COPD assessment test, modified medical research council (mMRC) score, spirometric classification, and HRCT were collected. COPD patients were classified into two groups: COPD with bronchiectasis and COPD without bronchiectasis. The clinical characteristics of both groups were compared. Results: Bronchiectasis was presented in 18.4% (nÂ =Â 64). The proportion of smokers, smoking index, and forced expiratory volume in 1 second predicted value were 62.5%, 27.3Â Â±Â 13.2, 48.2Â Â±Â 26.4, respectively, in the bronchiectasis group, which were lower than those of the group without bronchiectasis (82.0%, 32.6Â Â±Â 17.6, and 57.9Â Â±Â 18.8) (PÂ <Â 0.05). Complications, COPD assessment test (CAT) and the rate of CATâ¥10 in the bronchiectasis group were 2.8Â Â±Â 1.7,13.6Â Â±Â 7.4 and 26.6%, respectively, which were higher than those of the group without bronchiectasis (2.3Â Â±Â 1.5,11.3Â Â±Â 6.0, and 11.7%) (PÂ <Â 0.05). The proportion of type D (high-risk more-symptoms) in the bronchiectasis group was 50.0%; it was significantly higher than that of 35.7% in the group without bronchiectasis (PÂ <Â 0.05). Conclusions: COPD with bronchiectasis is associated with more complications, symptoms, and risks. More attention should be paid to the treatment of COPD with bronchiectasis to reduce the frequency of exacerbation and improve the health status. Keywords: Bronchiectasis, Chronic obstructive pulmonary disease, Combined assessment, High resolution computed tomography, Symptoms and risk